KARAKTERISTIK ZONE AGROEKOSISTEM DAN KESESUAIAN LAHAN DI LERENG SELATAN GUNUNG BATUKARU KABUPATEN TABANAN - I Wayan Rusna (Environmental Research Center (PPLH) of Udayana University, 2008)
The research of agroecosystem zone characteristics and land suitablities of south slope Batukaru Mountain, Tabanan Regency, Bali Province, was conducted. The aims of this research are to know the agroecosystem zone characteristics in toposequence of south slope Batukaru Mountain, their land suitablity classes, and limiting factors. This study was conducted through field survey by using zone or sub zone of agroecosystem as land unit in taking soil sample. Each of agrosystem zone or sub zone was observed and taken as the soil sample. The land characteristics were classified using the criteria of land characteristics classification in evaluating the land suitabilities. The land suitabilities, their potential, and limiting factors were analyzed using land suitability evaluation criteria. This study resulted in that south slope of Batukaru Mountain can be divided into 5 agroecosystem zones with various characteristics and land suitabilities. The main limiting factor in rice field was the lack of nitrogen, phosphate, and calium. On the other hand, in dried land, coconut farming, and coffee farming, the limiting factors were the lack of Nitrogen and the sloping land mainly in agroecosystem 3 and 4.